Left Lateral Positioning with Head Elevation Increase The Partial Pressure of Oxygen on Patients with Mechanical Ventilation - Karmiza Karmiza; Muharriza Muharriza; Emil Huriani (Jurnal Ners, 2014)
Introduction: Breathing literally means the movement of oxygen from the atmosphere and reach the cells and carbon dioxide into the atmosphere. Partial pressure of oxygen (pO2) is one of the important components in the process of respiration, especially in patients with mechanical ventilation. There are several interventions that can be performed in an effort to improve the ventilation, one of them is patients positioning: left lateral position with 30 degrees head elevation. This study aimed to determine the effect of left lateral position with 30 degrees head elevation to the value of partial pressure of oxygen in patients with mechanical ventilation in intensive care unit RSUP DR. M. Djamil Padang.Methods: This study was Pra Experiments with one group pretest posttest design. 15 samples taken by purposive sampling method. Data obtained by blood gasses analysis and it was conducted since May 8th untill June 5th, 2013. Univariate data presented in frequency distribution table, while the bivariate data using the paired T test. Result: Univariate analysis showed the value of the partial pressure of oxygen ( pO2 ) before intervention between 119-228 mmHg , while the value of the partial pressure of oxygen ( pO2 ) after intervention between 132-269 mmHg . Paired T test results showed a signifi cant difference between the value of the partial pressure of oxygen (pO2) before and after intervention (p = 0.040, p < 0.05 ).Discussion: The left lateral position with 30 degrees head elevation could increase the partial pressure of oxygen (pO2) in patients with mechanical ventilation.Results: The results of this study can be used for increasing the nursingcare quality of patients with mechanical ventilation in order to reduce the time of hospitalization. Further research on these positioning interventions can be developed for patients with primary respiratory problems or lung disease.